1983
DOI: 10.1002/aic.690290407
|View full text |Cite
|
Sign up to set email alerts
|

Chain‐of‐rotators equation of state

Abstract: Equations A4 and A5 have a feasible solution Dad > 0 i = 1,2,. . ,N ('48) if and only if the hyperplane defirxed by these equations intersects at least one of the planes bounding the positive region. Thus, at least one set of equations (A91 a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…Equations of this class are slightly more complex than the simple van der Waals equations, but they may be used to represent simultaneously liquid densities and vapor pressures for fluids containing large molecules. Extension to mixtures has been reported by several authors, notably Donohue and Prausnitz (1978), Chien et al (1983) and Kreglewski and Chen (1978).…”
Section: Introductionmentioning
confidence: 83%
“…Equations of this class are slightly more complex than the simple van der Waals equations, but they may be used to represent simultaneously liquid densities and vapor pressures for fluids containing large molecules. Extension to mixtures has been reported by several authors, notably Donohue and Prausnitz (1978), Chien et al (1983) and Kreglewski and Chen (1978).…”
Section: Introductionmentioning
confidence: 83%
“…An EOS similar to PHCT is the chain-of-rotators EOS (Chien et al, 1983;Kim et al, 1986). Variations of PHCT have been used extensively in representing phase equilibria for vaporphase polymer-monomer-solvent mixtures at high pressure as used, for example, in the production of polyethylene (Feng et al, 2001), as shown in Figure 13.…”
Section: Equations Of State (Eos)mentioning
confidence: 99%
“…One particular class of semitheoretical correlations is derived from the dense-fluid theories of Prigogine (1957) and Flory (1970). These correlations include the perturbed-hard-chain (PHC) equation (Beret and Prausnitz, 1975;Donohue and Prausnitz, 1978) and the chain-of-rotators (COR) equation (Chien et al, 1983). These equations contain physically significant molecular parameters that are obtained from pure-component thermodynamic data.…”
Section: Introductionmentioning
confidence: 99%